The Challenges and Difficulties in Teaching Listening: An Exploratory Research in a Junior High School in Kudus - Utomo, Slamet; Kusmaryati, Sri Endang; Sulistyowati, Titis (Language Circle: Journal of Language and Literature, 2019)
The objectives of this study are describing the process of teaching English (listening) and identifying the difficulties in teaching (English) listening in a Junior High School in Kudus. This research uses exploratory research design. I will explore qualitative data to analyze the process of the teaching and learning English in Kudus and to identify the need of the learning materials. The subjects of the research are five English teachers’ from a Junior High school in Kudus, they have been teaching English for more than ten years. They have been teaching from different classes, class 7, class 8, and class 9. This study has discovered the challenges and difficulties in learning and teaching in Junior High School in kudus. Most teachers feels that time management become their major challenge in organizing classroom. They have set lesson plan, but sometimes the lesson does not work exactly the same. They have to work with mixed-level students, with students with learning difficulties, and with learners who are coming from different backgrounds. Teachers should be aware that it is part of teachers’ primary duty to cope with every student. Most students can learn a foreign language to some level, but there are many reasons why their improvements are not achieved significantly.